Kebijakan Pemerintah Daerah dalam Pemberdayaan Pasar Tradisional di Kabupaten Sleman Tahun 2018 - Puguh Saputra; Muhammad Eko Atmojo; Vindhi Putri Pratiwi (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
The development of modern shops or lined shops has recently grown rapidly to various regions, including in Sleman Regency. This will be a new problem for the economic sector, wherewith the existence of various modern shops or networked shops will have an impact on the weakening of the existing traditional markets in the region. So that there needs to be a role from the government to be able to carry out strategies in increasing the existence of traditional markets in the community. Consequently, the purpose of this research is to examine regional government policies in empowering traditional markets in the Sleman Regency Government. Where in Sleman Regency, there are currently several traditional markets that are dead or not running. From the results of the study, it was found that to keep increasing the extension of traditional markets so as not to be confused with modern markets, the Sleman Regency Government implemented a clear policy foundation, namely Perda No 17/2012, Perda No 18/2012, and Perda No 54/2015. Keywords : Policy, Empowerment, Traditional Market